2009
DOI: 10.1186/1471-2458-9-84
|View full text |Cite
|
Sign up to set email alerts
|

Maternal care and birth outcomes among ethnic minority women in Finland

Abstract: Background: Care during pregnancy and labour is of great importance in every culture. Studies show that people of migrant origin have barriers to obtaining accessible and good quality care compared to people in the host society. The aim of this study is to compare the access to and use of maternity services, and their outcomes among ethnic minority women having a singleton birth in Finland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(159 citation statements)
references
References 62 publications
10
144
3
2
Order By: Relevance
“…In Finland, African-origin singleton newborns had a 6-fold increased perinatal mortality rate compared to newborns of native mothers [9]. Somali women in Sweden carried a higher risk of perinatal mortality, neonatal distress, preterm delivery, and small-for-gestational-age neonates [10].…”
Section: Introductionmentioning
confidence: 99%
“…In Finland, African-origin singleton newborns had a 6-fold increased perinatal mortality rate compared to newborns of native mothers [9]. Somali women in Sweden carried a higher risk of perinatal mortality, neonatal distress, preterm delivery, and small-for-gestational-age neonates [10].…”
Section: Introductionmentioning
confidence: 99%
“…Limited access to health care has been related with worse reproductive results (prematurity, low birth weight) in immigrant populations [30][31][32][33] . A change along the period in the method used for gestational age determination might have an impact on the estimated gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of migrant women in Finland showed a notable variation in health and in the use of services within different migrant groups as compared to the rest of the population [13]. Likewise, in Denmark in 1981-2003 stillbirths and infant mortality were higher among some ethnic groups, but not among others [14].…”
Section: Elina Hemminkimentioning
confidence: 99%